Paravaginal defect: A new classification of fascial and muscle tears in the paravaginal region - Otcenasek, Michal; Gauruder-Burmester, Annett; Haak, Lucia A; Grill, Robert; Popken, Gralf; Baca, Vaclav (Clinical anatomy (New York, N.Y.), 2016)
The lateral support of the vaginal wall depends on the integrity of the paravaginal section of the visceral pelvic fascia, levator ani, and their connection. Various defects of the muscle and fascia can result in identical clinical findings-ie, the descent of the lateral vaginal sulcus. In this study, we created a realistic scheme for classifying paravaginal defects, based on the complex relationship of the pelvic fascia with the levator ani. Surgical observations, cadaver examinations, and a complex magnetic resonance imaging (MRI)-based 3-dimensional (3D) model were used to analyze the spatial relationships of normal and defective anatomy of the female pelvic floor. Descent of the lateral vaginal sulcus can result from a defect in the paravaginal visceral pelvic fascia, levator ani, or both. The fascial defect can be partial or complete, and the muscle defect can vary in location. A detailed illustrated classification is presented. We present a new model of the pathology that underlies a common clinical finding.
Keywords: Muscles; Wounds and Injuries; lidé středního věku; Fascia; avulsion; Humans; visceral pelvic fascia; rány a poranění; Middle Aged; senioři; paravaginal defect; Female; magnetická rezonanční tomografie; Imaging, Three-Dimensional; pánevní dno; levator ani; Aged; zobrazování trojrozměrné; endopelvic fascia; ženské pohlaví; vagina; Magnetic Resonance Imaging; Adult; Vagina; svaly; dospělí; lidé; fascie; Pelvic Floor